Off-pump coronary artery bypass with heparin in a patient with a history of heparin-induced thrombocytopenia: a case report - Yuya Ito; Aya Saito; Yuki Shirai; Noboru Motomura (Surgical Case Reports)
Abstract Background Cardiovascular surgery for patients with a history of heparin-induced thrombocytopenia (HIT) with thrombosis requires careful perioperative anticoagulation therapy. When cardiovascular surgery is required for patients having ‘remote’ HIT, such as those who had a history of HIT and platelet factor-4/heparin antibodies turned out to be negative, it is recommended that re-exposure to heparin should be limited only to the intraoperative phase. However, few case reports have described detailed strategies for perioperative anticoagulation regimens. Case presentation We present the case of a 76-year-old woman, presenting with unstable angina pectoris and requiring coronary artery bypass grafting. She had a history of cardiac resuscitation and percutaneous coronary intervention for unstable angina pectoris with ventricular tachycardia 7 years prior, which caused HIT with thrombosis resulting in amputation of four fingers. On admission, platelet factor-4/heparin antibodies, biomarkers for HIT were not detected; the platelet count was 18.0 × 104/µl. Off-pump coronary artery bypass grafting was performed using heparin; argatroban infusion was continued until 9 h prior to the operation and restarted 3 h postoperatively, bridged with regular warfarin from 4 days to 3 months postoperatively. Platelet factor-4 /heparin antibodies were detected on postoperative day 8 without any clinical symptoms and became negative by day 91. Conclusion We consider this anticoagulation strategy is effective especially in countries, where bivalirudin is not available. Re-exposure to heparin in cardiovascular surgery for patients with a history of ‘remote HIT’ is reasonable, and appropriate anticoagulation is important for an uneventful postoperative course.